Serum Lactate Dehydrogenase Is a Novel Predictor for the Severity in the Patients With MAFLD: A Cross-Sectional Study in Hefei, China - Yu L; Bao S; Zhu F; Xu Y; Zu F; Liu Y; Jiang R; Chen S; Chen W (Diabetes, Metabolic Syndrome and Obesity)
Liang Yu,1,* Shiming Bao,2,* Feng Zhu,3,* Yanyan Xu,1 Fuqiang Zu,1 Yanwei Liu,1 Runbeng Jiang,1 Wei Chen,4 Song Chen5 1Department of General Surgery, The Second Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 2Department of Emergency Surgery, Tongling People’s Hospital, Tongling, People’s Republic of China; 3Department of General Surgery, Tongling People’s Hospital, Tongling, People’s Republic of China; 4Department of General Surgery, the First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 5Department of General Surgery, the Affiliated Chuzhou Hospital of Anhui Medical University (The First People’s Hospital of Chuzhou), Chuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Song Chen, Department of General Surgery, the Affiliated Chuzhou Hospital of Anhui Medical University (The First People’s Hospital of Chuzhou), Chuzhou, People’s Republic of China, Email chensong101425@163.com Wei Chen, Department of General Surgery, the First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China, Email 13665560109@163.comBackground & Aims: The aim of this study was to assess the association between the level of lactate dehydrogenase (LDH) and the severity of metabolic syndrome (MetS) and Metabolic Associated Fatty Liver Disease (MAFLD) and the potential diagnostic value of LDH for identifying at-risk metabolic associated steatohepatitis (MASH).Methods: This cross-sectional, real-world retrospective study enrolled a total of 1118 obese patients in the department of bariatric surgery at the Second Affiliated Hospital of Anhui Medical University from January 1, 2018, to December 31, 2021. Of these, 855 were enrolled in the study cohort. MAFLD was defined as the presence or absence of fatty liver disease as suggested by histologic biopsy of liver or postoperative pathology slides, or even hematology, and meets one of the following three conditions: overweight or obesity, T2DM, and metabolic dysfunction (MetS). Serum LDH activity levels were measured in 885 patients, and logistic regression was used to analyze the relationship between LDH and metabolic syndrome and the severity of MAFLD.Results: In the study cohort of 855 obese patients, 604 (70.6%) had MetS. Patients with MetS (214.1[209.0– 219.2]) had significantly higher serum LDH levels than those without MetS (188.7[181.6– 195.9]). Particularly, serum LDH level was significantly higher in subjects with hypertension, central obesity, diabetes mellitus or hyperglycemia, elevated levels of triglycerides, or reduced levels of high-density lipoprotein than in those without. Moreover, LDH concentrations were grouped according to the total number of MetS components present in each patient, with Serum LDH levels gradually increase with the total number of MetS components. The MASH subjects had significantly higher LDH levels than the other three less severe non-MASH cohorts, including normal liver, simple fatty steatosis, and B.MASH. Logistic regression showed that LDH was significantly and positively correlated with MAFLD, B.MASH, MASH, at-risk MASH, fibrosis grade ≥ 1, fibrosis grade ≥ 2 and fibrosis grade ≥ 3.Conclusion: Increased LDH levels were significantly and independently associated with the presence and severity of metabolic syndrome and MAFLD, indicating that LDH could be used as a novel biomarker and clinical predictor of severity of metabolic syndrome and MAFLD.Keywords: lactate dehydrogenase, obesity, metabolic syndrome, inflammation, metabolic associated fatty liver disease, (MAFLD)